2015
DOI: 10.1111/cge.12601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a counselling strategy for diagnostic WES in paediatric neurology: an exploration of parents' information and communication needs

Abstract: As whole exome sequencing (WES) is just starting to be used as a diagnostic tool in paediatric neurology for children with a neurological disorder, and patient experiences and preferences with regard to counselling are relatively underexplored. This article explores experiences and preferences of parents with pre-test and post-test counselling in a trial that uses WES for diagnostics. Second, it maps information and communication needs which exceed the counselling protocol, in order to acquire insight into how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…This may complicate the counselling process. Our research suggests that it may be advisable to prepare parents in advance for this continued uncertainty after obtaining the test results, and to provide them with follow-up care in order to deal with the concerns and questions raised by the results (Krabbenborg et al 2015). Furthermore, counsellors can re-contact parents and inform them when new literature about their child’s disease becomes available in order to diminish their uncertainty (see also Reiff et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may complicate the counselling process. Our research suggests that it may be advisable to prepare parents in advance for this continued uncertainty after obtaining the test results, and to provide them with follow-up care in order to deal with the concerns and questions raised by the results (Krabbenborg et al 2015). Furthermore, counsellors can re-contact parents and inform them when new literature about their child’s disease becomes available in order to diminish their uncertainty (see also Reiff et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that the identification of potential diagnostically relevant sequence variants in the parents (e.g., X-linked recessive mutations in mothers) leads to new questions and uncertainties. Yet, we have previously shown that the desire of parents to identify the cause of their child’s disease nullifies any pre-test distress on the potential risk of identifying any medically relevant genetic variants in their own DNA (Krabbenborg et al 2015). This combination of factors indicates that sufficient amounts of time should spent in pre- and post-test counselling to ensure parents understand the potential risks of the test and how such potential risks may affect their lives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetics professionals often focus on communicating genome-based scientific information with less attention to nuanced and variable psychosocial issues [14,17,18]. Such communication involves heavy use of technical jargon that may overwhelm, confuse and frustrate families [19] whose primary concerns center on medical management, daily care and quality of life [20,21]. …”
Section: Introductionmentioning
confidence: 99%